Different sources and doses of walnut leaves and mixed fruit leaves on compost quality, tested through germination tests using white mustard (Sinapis alba) as the test plant species - Tirczka, Imre; Hayes, Matthew (JOURNAL OF LANDSCAPE ECOLOGY, 2012)
The effects of compost derived from walnut leaves has for a long time been a theme of contention. In our trials we examined whether incorporating walnut leaves had an effect on composting rates and whether there were noticeable negative effects arising from the dosage of walnut leaves on compost quality, as demonstrated by effects on the development of white mustard (Sinapis alba) as a test plant. No significant effects were seen for differences (neither positive nor negative) between tested walnut leaf leafmould when compared with other mixed fruit tree leafmoulds in any of the combinations. Where negative effects from compost were seen, these were primarily seen as growth development effects and not effects on germination. The negative effects on plant growth from certain composts were observed mainly on those treatments where there were higher dosage of undecomposted leaf material. At the same time, no significant negative effects were observed from composted treatments as compared with the control after four months, and of the negative growth developments which were observed, these could rather be put down to nutrient deficiencies resulting from the quartz-sand growth medium. 9 months after composting, still neither the walnut nor the mixed fruit leafmoulds showed any negative effects on plant mass. Moreover, the treatment composts from the trial demonstrated between 1.6 to 3.8 times higher growth rates compared with the control. We can be confident in using leafmould prepared from walnut leaves, and see no negative effects from using walnut leaf derived composts of 9 months or more.